Investment Cooperation in the Conditions of Globalization: Problems and Prospects for the Development - Muminov, Nozim; Hoshimov, Pazliddin; Muxitdinova, Nasiba; Umarov, Okil (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the aim of the study is to systematize theoretical views and identify trends in attracting foreign direct investment in national economies in the context of globalization of the world economy. When conducting this research the methods of macroeconomic and system analysis, comparative and statistical analysis, a logical, historical and evolutionary approach, grouping and scientific generalization and others have been used. The main results of this study are: the differences and one-sidedness of the theoretical positions with respect to determining the essence of internationalization and globalization of the world economy are revealed; the theoretical directions of improving investment cooperation are disclosed; there was developed the conceptual foundations of an integrated approach to globalization, as a stage in the development of the internationalization of production and investment cooperation; features of direct foreign investment at different stages of internationalization of exchange and production are established; within the framework of a systematic approach to globalization and the development of foreign direct investment, analytical assessments of foreign direct investment (FDI) at different stages of internationalization have been carried out; the role of TNCs in the development of globalization and foreign direct investment is justified; comparative advantages of the practice of using FDI in various regions of the world, and in particular in Malaysia, have been identified; the most important factors and ways to increase the investment attractiveness of the Republic of Uzbekistan are justified.